Covalent Cross‐Links Enable the Formation of Ambient‐Dried Biomass Aerogels through the Activation of a Triazine Derivative for Energy Storage and Generation. (27th July 2022) - Tang, Songsong; Ma, Mingze; Zhang, Xujing; Zhao, Xuan; Fan, Juncheng; Zhu, Penghui; Shi, Kaiyuan; Zhou, Jian
Abstract: Aerogels hold promises as lightweight replacements in various applications but are plagued by their fabrication equipment, such as supercritical dryers or lyophilizers that need to work under extreme conditions. This study presents a covalent chemistry approach to strengthen cellulose nanofibers (CNF) with carboxymethylated chitosan (CMCs) to produce aerogels by ambient drying. The cross‐linking and gelation of the CNF and CMCs solutions are triggered by a triazine derivative, 4‐(4, 6‐Dimethoxy[1.3.5]triazin‐2‐yl)‐4‐methylmorpholinium chloride hydrate, to form an amide bond. This approach leads to robust hydrogels that can resist capillary force during the ambient volatilization process and are turned into aerogels by freezing, solvent thawing and exchange, and ambient drying. The lightweight aerogels exhibit desirable qualities, including superior mechanical performance, a low density of 12.0 mg cm −3, and low shrinkage of 10.1%. The presented CMCs/CNF aerogels can also serve as a helpful carrier for conductive polymer, poly (3, 4‐ethylene dioxythiophene):tosylate, through in situ polymerization to demonstrate their applications. These conductive aerogels are used for high‐performance supercapacitors and moisture‐enabled electrical generators. This study provides inspiration and a reliable approach for the elaborately structural design of aerogels at ambient conditions and endows application prospects in energy storage and generation opportunities. Abstract : Covalent chemistry strengthens cellulose nanofibers with carboxymethylated chitosan to produce aerogels by ambient drying. It exhibits desirable qualities, including superior mechanical performance, a low density of 12.0 mg cm −3, and low shrinkage of 10.1%. Serving as a helpful carrier for conductive polymer, poly (3, 4‐ethylene dioxythiophene):tosylate, to demonstrate their applications. These conductive aerogels are used for high‐performance supercapacitors and moisture‐enabled electrical generators.